Dampak Zakat Terhadap Kesejahteraan Umat - Hasibuan, Devi Imelda Sahfitri; Batubara, Sarmiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Zakat is obligatory to be paid by every Muslim. Not only as an Islamic pillar zakat is also an important instrument in building the country’s reeconomy. Islamic history has proven the effectiveness of zakat in alleviating poverty. Looking at the estimation of the potential of zakat in Indonesia and the reality in society, it seems that there is a gap between the rich and the poor. The potential of zakat funds in Indonesia is estimated to reach Rs. 200 trillion, while the poverty rate in Indonesia is still high. The meaning of managed zakat funds is still far from its predicted potential. BAZNAS as the state zakat management agency sees that there are several factors that make the management not yet optimal. One is the minimum trust of the muzakkis that arises because the reporting of the management of zakat funds by the zakat amil agency has not been transparent. In addition to seeking to improve public trust, BAZNAS implements programs in the areas of health, education, and community welfare. Thanks to these efforts, the poverty rate in Indonesia is gradually decreasing and in the future it is expected to eradicate poverty in Indonesia.